Health Informatics Training at the University of Missouri - Balas, E.A.; Reid, J.C.; Mitchell, J.A. (Yearbook of Medical Informatics, 1997)
Health informatics training has a long tradition at the University of Missouri. The current program prepares future researchers for the rapidly changing field of health informatics. This paper describes the training program, the fellowships, the interdisciplinary strengths of the program, and representative projects. Research opportunities range from information analyses of basic medical sciences through development of clinical information systems to the evaluation of information systems. The informatics training program at the University of Missouri promotes evidence-based medical informatics and has a strong emphasis on the organizational aspects of successful information system implementation.
Keywords: Medical Informatics Training